Anterior and posterior segment parameters measured with Fourier domain optical coherence tomography in photopic and scotopic conditions - Rampersad, Nishanee (Indian J Ophthalmol, 2016)
PURPOSE: To compare anterior and posterior segment parameters measured with the iVue-100 optical coherence tomography (OCT) in photopic and scotopic conditions. METHODS: Central and peripheral corneal thickness, retinal nerve fiber layer and macula thickness were measured using the iVue-100 OCT in 47 healthy individuals at a higher education institution in photopic (958 lux) and scotopic (0.03 lux) conditions. RESULTS: As the lighting conditions changed from scotopic to photopic, a significant change in pupil size was noted (P < 0.001). However, there was no significant difference in central corneal thickness measurements with this change in surrounding illumination with only the temporal peripheral corneal area showing a significant difference (3.44 μm thinner). No significant differences were found in the retinal nerve fiber layer thickness. A significant decrease in the reading was noted in only the inferior (P = 0.05) and temporal (P = 0.05) inner macula area. CONCLUSION: Change in the ambient lighting conditions does not result in a clinically significant difference in corneal, retinal nerve fiber layer, and macula thickness when measured with the iVue-100 OCT.